PENGARUH PERENCANAAN PAJAK TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Diah Fajri Hanifah; Sri Ayem (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This writing is done to examine and understand partially thee effeect of tax planniing and performancce financial on Value Firm. To study and understand the effect of tax planning on financial performance. To study and understand the effect of tax planning on firm value through the financial performance of food and beverage companies on the Indonesia stock exchange for the 2015-2019 period. This study took a sample of Food and Beverage companies listed on the Indonesia Stock Exchange. The type of data used in conducting this research is secondary data in the form of company annual financial reports. During the 2015-2019 period, there were 13 samples of Food and Beverage companies. The sampling method used in this study was purposive sampling, which is a research sampling method based on certain criteria. Multiple and simple linear regression data analysis techniques are significant at 5% level. The results of this study indicate (1) tax planning has a significant positive effect on firm value, (2) financial performance has a significant positive effect on firm value, (3) tax planning has a significant positive effect on financial performance, (4) tax planning and financial performance simultaneously has a significant positive effect on firm value, (5) financial performance is able to positively strengthen the relationship between tax planning and firm value.